2013
DOI: 10.1007/978-1-62703-523-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pyroptosis by Measuring Released Lactate Dehydrogenase Activity

Abstract: Summary Pyroptosis is a form of programmed, inflammatory cell death that is dependent on the activation of a cysteine protease Caspase-1. In this chapter, we describe an enzymatic assay for the detection of lactate dehydrogenase (LDH) released by dead or dying cells during pyroptosis using a commercially available kit. We also discuss another simple and cost-effective method to measure LDH adapted from Decker et al.(1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 9 publications
(10 reference statements)
4
101
1
1
Order By: Relevance
“…Induction of pyroptosis is characterized by activation of caspase-1, loss of integrity of cell membrane, and release of lactate dehydrogenase (LDH) which is normally maintained within the cell cytosol. Thus the release of intracellular LDH is recognized as an effective methodology to define the occurrence of pyroptosis [14], which was performed in this study to define whether pyroptosis was induced. Our data showed that pyroptosis in these AIM2 overexpressed cells was induced in a time-dependent manner (Figure 3I).…”
Section: Resultsmentioning
confidence: 99%
“…Induction of pyroptosis is characterized by activation of caspase-1, loss of integrity of cell membrane, and release of lactate dehydrogenase (LDH) which is normally maintained within the cell cytosol. Thus the release of intracellular LDH is recognized as an effective methodology to define the occurrence of pyroptosis [14], which was performed in this study to define whether pyroptosis was induced. Our data showed that pyroptosis in these AIM2 overexpressed cells was induced in a time-dependent manner (Figure 3I).…”
Section: Resultsmentioning
confidence: 99%
“…One of the main morphological features of pyroptosis is loss of the integrity of the plasma membrane, which leads to cell lysis and the release of cellular contents to the surroundings1644. Lactate dehydrogenase (LDH) is an enzyme that is normally sequestered inside the cell and is released extracellularly only in the event of cell lysis45. Measuring the activity of LDH in the medium of the cultured cells is a useful tool for detecting lytic cell death, including pyroptosis45.…”
Section: Resultsmentioning
confidence: 99%
“…Supernatant samples were collected at the indicated time points in figures. Cytotoxicity was defined as the percentage of total lactate dehydrogenase released into the supernatant and was determined as described (Rayamajhi et al, 2013b). IL-1β secretion was determined by enzyme-linked immunosorbent assay (ELISA) (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%